2019
DOI: 10.1021/acscombsci.9b00004
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Benz-Fused Azoles via C-Heteroatom Coupling Reactions Catalyzed by Cu(I) in the Presence of Glycosyltriazole Ligands

Abstract: Glycosyl triazoles are conveniently accessible and contain multiple metal-binding units that may assist in metal-mediated catalysis. Azide derivatives of d-glucose have been converted to their respective aryltriazoles and screened as ligands for the synthesis of 2-substituted benz-fused azoles and benzimidazoquinazolinones by Cu-catalyzed intramolecular Ullmann type C-heteroatom coupling. Good to excellent yields for a variety of benz-fused heterocyles were obtained for this readily accessible catalytic system. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 64 publications
(37 reference statements)
2
35
0
Order By: Relevance
“…[14][15][16][17] Considerable efforts have been devoted to the copper-catalyzed synthesis of benzimidazole derivatives, [18][19][20][21][22] in which the cyclization of ohaloarylamidines has drawn much attention. [23][24][25][26][27][28][29] Herein, we explored the idea to build the key bis-benzimidazole structure of telmisartan via the copper-catalyzed cyclization of o-haloarylamidines, 30,31 which were accessible to be obtained from ohaloarylamines (Scheme 2). This approach was suitable to produce telmisartan with good overall yield while avoiding the shortcomings associated with the reported routes.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Considerable efforts have been devoted to the copper-catalyzed synthesis of benzimidazole derivatives, [18][19][20][21][22] in which the cyclization of ohaloarylamidines has drawn much attention. [23][24][25][26][27][28][29] Herein, we explored the idea to build the key bis-benzimidazole structure of telmisartan via the copper-catalyzed cyclization of o-haloarylamidines, 30,31 which were accessible to be obtained from ohaloarylamines (Scheme 2). This approach was suitable to produce telmisartan with good overall yield while avoiding the shortcomings associated with the reported routes.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, one of the advantages of di-O-isopropylidene gluco-and allofuranose derivatives is that these compounds could be selectively deprotected to generate diols that can be subsequently functionalized for their use in different fields of scientific research. Tiwari and co-workers [41] reported the synthesis of a series of glycosyl triazoles and their evaluation as efficient ligands in Cheteroatom coupling reactions by using a mono-O-isopropylidene glucofuranose derivative as starting material. Srinivas et al [42,43] reported a 1,2,3-triazole-linked allofuranose compound that can be a key intermediary in the preparation of a series of heterocyclic-containing carbohydrate-triazole hybrids with potential antimicrobial activity.…”
Section: Resultsmentioning
confidence: 99%
“…Tiwari et alreported a d ‐glucose‐based triazolyl derivative as an efficient ligand in copper‐catalyzed double condensation reactions to give 2‐( N ‐arylamino)benzothiazoles in 80–98 % yields [Eq. (65)].…”
Section: Condensation Of O‐haloaniline With Different Cyclization mentioning
confidence: 99%